Effect of sucrose and lactose on Streptococcus mutans biofilm adherence - Nuraini, Prawati; Wahluyo, Soegeng; Saroso, Thania Y. (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2026)
Background: In Indonesia, 67.3% of 5-year-old children have dental caries, a prevalent oral illness, with a decayed, missing, and filled teeth index score of 6 or above. Breast milk contains approximately 7% lactose, cow’s milk 4.6%, and first formula milk between 5.4% and 8.2%. Lactose and sugar, however, can aid in the development of Streptococcus mutans, a bacterium linked to dental caries. Purpose: The aim of this study is to examine the differences in S. mutans biofilm adherence after biofilm induction with 5% sucrose and 8% lactose. Methods: Streptococcus mutans biofilms were generated for 24 hours at 37°C using Brain Heart Infusion Broth (BHIB) medium with 5% sucrose and 8% lactose. The optical density value was determined by measuring the amounts of adherent bacteria at 570 nm using a spectrophotometer. The study results were statistically analyzed using variance tests, followed by Tukey’s honest significant difference test (p < 0.05). Results: Streptococcus mutans biofilm induced by sucrose had a higher adherence value than that caused by lactose. There were no significant differences in BHIB with S. mutans and 5% sucrose or 8% lactose (p = 0.100; p < 0.05). Conclusion: Streptococcus mutans induced by 5% sucrose and 8% lactose affected the adherence of bacterial biofilms, but there was no difference in bacterial biofilm adherence between the two compounds. Subsequent research revealed that sucrose and lactose components influenced biofilm adherence.